Cultivation of medical student’s science popularization ability in teaching of pharmacy - ZHANG Ying, FANG Hongjuan (Jichu yixue yu linchuang, 2023)
The scientific popularization of pharmacy knowledge is one of the important directions for the transformation of pharmaceutical services in China. As the main force of the future pharmaceutical popular science information dissemination, the capacity building of popular science of college students is crucial. This article discusses the necessity and significance of improving the capacity of pharmacy college students in popular science based on current situation and gives some suggestions on how to integrate the education in medical colleges, clinical pharmacists and pharmacy colleges to improve the pharmacy college students’ popular science capacity. The recommended strategy is to strengthen the cultivation of students’ popular science awareness and sense of social responsibility, makes them to be competent in pharmaceutical popular science education and serves the general public in their future work to build a “Healthy China”.